ANALISIS YURIDIS MENGENAI SENGKETA KEDUDUKAN PENYEWA TANAH (STUDI TERHADAP PUTUSAN PENGADILAN NEGERI MEDAN NO.562/PDT.G/1995/PN-MDN) - AUDI YULIAN MAHDI (PREMISE LAW JURNAL, 2017)
ABSTRACT The right to lease a building is the right of a person or a legal entity to construct and to have a building on a piece of land owned by other person by paying for the rent for a certain period of time which is agreed by both parties. In the case of the right to lease, the owner hands over his empty land to a tenant so that the latter can build a building on it. The leasing relation between the land owner and the tenant will not be broken off when the leasing object is sold by the owner. The leasing contract made orally by the land owner and the tenant did not cause the tenant’s rights vanished. The land right transfer which became the leasing object should not break off the leasing. The tenant could file compensation if the land he was renting would be sold without his knowledge, and had the right to pull down the house he had built and take it away with him. He had the right to own his own home which he had built on the leasing land. Keywords: Right to Lease, Leasing, Contract